2018
DOI: 10.3390/met8110900
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Simulations of Pure Tin Based on a New Modified Embedded-Atom Method Interatomic Potential

Abstract: A new interatomic potential for the pure tin (Sn) system is developed on the basis of the second-nearest-neighbor modified embedded-atom-method formalism. The potential parameters were optimized based on the force-matching method utilizing the density functional theory (DFT) database of energies and forces of atomic configurations under various conditions. The developed potential significantly improves the reproducibility of many fundamental physical properties compared to previously reported modified embedded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…It has been reported that this method can significantly improve the overall performance of developed interatomic potentials [31][32][33]. In this study, we particularly extend our recent work [24] on the development of an interatomic potential for pure Sn-based on the force-matching method. We will present a detailed process for the development of interatomic potential that realizes the atomistic simulations of the Ag-Cu-Sn ternary system.…”
Section: Early Career Scholars In Materials Science 2022mentioning
confidence: 69%
See 4 more Smart Citations
“…It has been reported that this method can significantly improve the overall performance of developed interatomic potentials [31][32][33]. In this study, we particularly extend our recent work [24] on the development of an interatomic potential for pure Sn-based on the force-matching method. We will present a detailed process for the development of interatomic potential that realizes the atomistic simulations of the Ag-Cu-Sn ternary system.…”
Section: Early Career Scholars In Materials Science 2022mentioning
confidence: 69%
“…However, the MEAM potential for pure Sn developed by Ravelo and Baskes [23], which underlies the previous development of alloy potentials [17][18][19][20][21][22], exhibits deficiencies in reproducing properties of the β-Sn phase that is stable at ambient conditions [24]. Moreover, the previous MEAM potentials for alloy systems [17][18][19][20][21][22] were not developed considering various physical properties of binary and ternary alloy systems, and the optimization of potential parameters was not systematically performed.…”
Section: Early Career Scholars In Materials Science 2022mentioning
confidence: 99%
See 3 more Smart Citations